Improving Product Quality and User Satisfaction through Early Customer Feedback - Cabral, Matías (2010)
New users of cluster computing find a high entry barrier due to the daunting complexity of deploying and managing a cluster. The Intel® Cluster Ready program aims to lower such entry barrier by setting standards for the cluster integration process and providing tools to simplify the deployment process. The Intel Cluster Checker tool, a key component of the Intel Cluster Ready program, is an automated and flexible tool that validates the cluster settings against the Intel Cluster Ready specification, and checks the general wellness of the cluster. This experience report shows how the product engineering team of Cluster Checker faced the challenge of having a small team and be able to provide a cutting-edge high-quality product in less time, maximizing resource usage, and increasing and securing early validation with key stakeholders.